2014
DOI: 10.3892/mmr.2014.2344
|View full text |Cite
|
Sign up to set email alerts
|

CD8+HLA-DR+ T cells are increased in patients with severe aplastic anemia

Abstract: The aim of the present study was to investigate the number and function of CD8+HLA-DR+ cells, which are considered to be activated cytotoxic T lymphocytes (CTLs), in peripheral blood to further examine the pathogenesis of severe aplastic anemia (SAA). Thirty-eight patients with SAA were included in the present study. Patients were screened for paroxysmal nocturnal hemoglobinuria by flow cytometry using anti-CD55 and anti-CD59 antibodies. The number of CD8+HLA-DR+ T cells was measured by three-color flow cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 22 publications
0
47
0
Order By: Relevance
“…CD45RA þ CCR7 À , CD45RA þ CCR7 þ , CD45RA À CCR7 À , and CD45RA À CCR7 þ cells were identified as effector T cells, naïve T cells, effector memory T cells, and central memory T cells, respectively [31]. HLA-DR was identified as an active marker on T cells [32]. Data were analyzed using BD Diva software (BD Biosciences).…”
Section: Surface Immunophenotypingmentioning
confidence: 99%
“…CD45RA þ CCR7 À , CD45RA þ CCR7 þ , CD45RA À CCR7 À , and CD45RA À CCR7 þ cells were identified as effector T cells, naïve T cells, effector memory T cells, and central memory T cells, respectively [31]. HLA-DR was identified as an active marker on T cells [32]. Data were analyzed using BD Diva software (BD Biosciences).…”
Section: Surface Immunophenotypingmentioning
confidence: 99%
“…These results are consistent with previous reports describing increased GZMB and IFN-γ expression in CD8 + T cells of AA patients. 2,27 We speculated that transfusion might affect the miRNA signatures in T cells as a result of allogenic antigen exposure in AA patients. 28 We, therefore, also examined miRNA profiles of T cells from age-matched healthy donors and patients with transfusion-dependent SCD and low-risk MDS for comparison with AA.…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation and over activation of cytotoxic T lymphocytes (CTLs; CD8+ T cells) are the direct causes of bone marrow failure in patients with SAA [2]. Our group conducted a series of studies in which we found abnormal expression of various immunomodulatory molecules on the surface of CTLs and an increased number of activated effective T cells (CD8+ human leukocyte antigen D related + T cells), with obviously higher levels of intracellular molecules, including perforin, granzyme B, tumor necrosis factor (TNF) β , and FasL, which confirmed that CTLs may be key cells in the pathogenesis of SAA [35]. A variety of viruses are known to lead to hyperfunction of CTLs via disruption of the immune balance and ultimately contribute to the occurrence of SAA.…”
Section: Introductionmentioning
confidence: 93%